(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Timeless Cafe is a business wherein a bookstore and a café come in one that will use eco-friendly straw such as rice straw instead of plastic straws to protect our environment. It is also a place where you can relax while enjoying products coffee, tea, and snacks, which can satisfy your hunger and provide health benefits. The researchers came up with this business because most of the researchers love milk tea, coffee, and food especially when they are stressed. It is a partnership type of business with a total capital of Php 1,500,000. Timeless Café is located at #38 Old Sauyo Road, Novaliches, Quezon City. The research method used was descriptive. By the use of a mixed method, the proponents surveyed50 respondents along with the business location. It also utilized financial statements in identifying the feasibility of the business and also considered SWOT analysis. The strengths of Timeless Café include products that are in demand and profitable, it is a healthy product, and the location is accessible. The company’s weakness is customer loyalty because the business is new in the area, and competitors have more loyal customers. The opportunities of the business are to be a franchise in the local market, provide job opportunities, and offer affordable products. The threats of the business are the existing competition, increasing operation costs, and price war. Out of 50 respondents, 46% like to drink coffee or milk tea while reading. With the idea of combining the café and bookstore,60% of respondents answered that it was very acceptable. Respondents who liked fries accounted for 46%, 22% of the respondents liked nachos, 10% of the respondents liked burgers, and 6% of the respondents chose bread and cakes. A total of 56% of the respondents answered that they are willing to buy the product offerings with the starting price of 80 pesos. A total of 100% of respondents answered that discount coupons will influence their purchasing decision. A total of 100% of respondents were willing to visit the store in the said location. The projected financial aspect of the business revealed that under the best scenario, the return on investment (ROI) was 59% during the fourth year of the business and 60% in the fifth year. Meanwhile, its average scenario revealed that the ROI was 24% in the fourth year of the business and 33% in the fifth year. One problem that limits the business is that the competitors have more loyal customers. Timeless Café should extend its capacity to reach the demand and expectation of the customers by offering new product flavors and price-worthy products and create promotional tools.